Design of 5S and ATS to reduce costs in a metal-mechanical company - Murrieta Guillen, Loretta Jasmir; Alva Alvarez, Maily; Díaz Díaz, Marco Antonio (LACCEI, 2024)
The present work was developed with the aim of addressing the issues of a metal-mechanic company in the production and logistics areas. The first identified issue was persistent disorder, while the second was labor incidents arising from unsafe practices by operators and a lack of training. This necessitates the need to address these encountered challenges. To do so, engineering tools such as 5S and ATS were respectively employed for each case. Ultimately, an annual cost reduction of $2,177.86 was achieved, along with a 69% reduction in downtime due to disorder. Additionally, the impact of implementing these tools was evaluated, resulting in a TIR of 13.72%, an NPV of $636.73, and a B/C ratio of 1.49.